VR communication simulation with scripted dialog elicits HPA axis stress - Ban, Yuki; Inazawa, Masahiro; Kato, Chisato; Warisawa, Shin’ichi (Frontiers in Virtual Reality, 2024)
Stress-inducing virtual reality (VR) systems have various applications in research, ranging from training to therapy to the observation of biological stress responses. Stress in VR can be evoked through environmental, cognitive, and social stimuli. Although various VR tasks can induce an autonomic nervous system (ANS) stress response, hypothalamic-pituitary-adrenal (HPA) axis stress responses have only been confirmed in VR for the virtual Trier social stress test (V-TSST).Understanding the impact of a wider variety of tasks on HPA-axis stress response could lead to the development of more effective stress relief measures and treatments. This study aims to clarify whether a virtual communication simulation, using a static procedure with a predetermined dialog, can evoke an HPA-axis stress response. Employing a virtual customer service system, we varied the intensity of the presented stress by changing the tone and gestures of the virtual customer. The findings confirm that HPA-axis stress responses can be elicited by such static virtual customer service training systems, and the stress responses can be adjusted by altering the avatar's attitude. These findings suggest potential applications in research for observing human physiological responses to stress and development of stress reduction strategies, thereby affirming the effectiveness of VR in communication training.